Dialectical nursing care: a concept analysis - Vargas Bitencourt, Julia Valeria de Oliveira; Furlan de Leo, Marcela Martins; Remiao Luzardo, Adriana; Biffi, Priscila; Sivirino Farias, Dilzilene Cunha; Santos Araújo, Jeferson (Investigación y Educación en Enfermería, 2025)
Objective. To analyze how the concept of dialectical nursing care is introduced in the scientific production of nursing. Methods. It is a concept analysis based on Rodgers’ evolutionary model. An integrative literature review was carried out for the identification and selection of articles, in January 2022 and updated in March 2024, limited to the period between January 2010 and December 2023. The search was conducted in six databases: PubMed, Web of Science, Embase, Science Direct, Scopus and LILACS, combining the descriptors Dialectics, Health and Care. Results. Based on Rodgers’ evolutionary model, it was possible to identify the attributes of the concept, which are: dialectical sensitivity, dialectical attitude, ambience and social determinants. The antecedents: The being and its social relationships, Health services, Work processes and Formative paradigm. The consequents: The being who cares for and the being cared for in their relationships, Work process and Formative paradigm. Conclusion. This study contributed to the clarification of the concept that proposes the analysis of dialectics in the social production of illness and health, operating syntheses and new syntheses, in order to overcome the contradictions that historically cross people, macrostructure and area of nursing knowledge.